THE EFFECTS OF 12-WEEK ISOKINETIC TRAINING ON KNEE STABILIZERS STRENGTH AND THE EFFICIENCY OF THE PERFORMANCE OF GYMNASTICS VAULTS - Adis Tabaković; Muhamed Tabaković; Almir Atiković (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
Abstract The aim of the research was to examine the effects of isokinetic training on knee stabilizer strength, and whether this increases the efficiency of performing basic gymnastics vaults. A total of 60 respondents, students of the Faculty of Sports and Physical Education (average age 19.7±1.5 years, weight 75.3±2.9 kg, height 179.8±6.7 cm) were included. The subjects were divided into two groups, experimental (EG) (n=30) and control (CG) (n=30). As part of the 12-week program, the experimental group (EG) in addition to exercises within the regular classes at the university had an additional concentric isokinetic training 3 times a week on the Biodex System 3 dynamometer, while the control group (CG) only had exercises within the regular classes at the university. The results showed statistically significant differences (p < 0.05) between (EG) and (CG), both, in increasing the strength of the knee stabilizers and in the performance of gymnastics vaults, and the strength of the knee extensors and flexors in favor of (EG). It can be concluded that the additional isokinetic training resulted in a greater increase in strength, but also a better performance of gymnastics vaults.